The contributory elements in natural access control of crime prevention in residential housing / Halmi Zainol ... [et al.] - Zainol, Halmi; Md Sakip, Siti Rasidah; Sazali, Muhamad Ferdhaus; Mohd Latif, Hafizah; Mohamad Bahari, Noor Ashikin (Universiti Teknologi MARA, Perak, 2022)
Various criminal problems surround us leading to discomfort in a residential area. Thus, this study focuses on how the contributory elements in natural access control can solve the problems of crime based on Crime Prevention Through Environmental Design (CPTED). The study aims to examine the layout of housing design that can cause crime in neighbourhoods area. Guideline and concepts of CPTED can improve the quality of life, reduce or prevent crime, and create a safe, secure living environment. The objectives are to identify the elements of CPTED that are related to natural access control, examine the contributory that influence based on natural access control in housing residential, and propose the characteristics of natural access control. Data collection was carried out by using observation and questionnaires. One hundred and thirty-one respondents have participated in this research. The study has found a lack of pedestrian walkways, good lighting, and moderate landscape elements contributing to natural access control